Specifying Distributed Graph Transformation Systems - Ranger, Ulrike; Schultchen, Erhard; Mosler, Christof (Electronic Communications of the EASST, 2007)
Graph transformation systems simplify software development by modeling the system in a visual and declarative language. Despite their expressiveness, they fail to support specifiers in modeling distributed systems. As software projects increasingly demand support for distribution, we aim to fill this gap for graph transformation systems. With our concepts, specifiers can visually specify graph transformations affecting multiple applications simultoniously. Based on this visual specification, the corresponding distribution to the different a pplications is automatically derived. We introduce our concepts in general and demonstrate their applicability by means of an example.